The Social Construction of Gender in the Experience of Vocational School Adolescents. A Critical Approach - Khabibah, Siti; Mutammimah, Heppy; Fajarman, Fajarman (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
In the context of vocational high schools, gender role divisions and stereotypes are often reinforced by the educational environment and social practices, which have an impact on career choices, social interactions, and future opportunities for adolescents, so this research aims to analyze how gender norms and stereotypes are formed and maintained in vocational high schools, identifies the social dynamics that influence adolescents' experiences of gender roles, presenting a critical approach to understanding and challenging the social construction of gender in educational institutions. It is also hoped that this research can provide important insight into how vocational education institutions become dynamic spaces in shaping adolescent gender identity. These findings also open a discussion regarding the importance of educational reform that is more inclusive and gender equal, so that it can encourage students to explore their potential without the limitations of gender stereotypes.Through a qualitative approach with in-depth interviews and participant observation, this research explores how patriarchal values, traditional gender norms, and educational policies implicitly shape adolescents' gender identity. This research concludes that the education system in vocational high schools is not gender neutral, but rather reproduces gender-based social injustice. Therefore, efforts are needed to deconstruct gender norms that exist in the curriculum and educational practices, in order to create a more inclusive and fair learning environment for all teenagers, regardless of their gender identity.